Pore Structure Fractal Characterization and Permeability Simulation of Natural Gas Hydrate Reservoir Based on CT Images - Hang Bian; Yuxuan Xia; Cheng Lu; Xuwen Qin; Qingbang Meng; Hongfeng Lu (Geofluids)
The gas-water two-phase seepage process is complex during the depressurization process of natural gas hydrate in a clayey silt reservoir in the South China Sea, the transport mechanism of which has not been clarified as it is affected by the pore structure. In this study, we select six clayey silt samples formed after the dissociation of natural gas hydrate in the South China Sea, employing CT scanning technology to observe the pore structure of clayey silt porous media directly. The original CT scanning images are further processed to get the binarized images of the samples, which can be used for simulation of the porosity and absolute permeability. Based on the fractal geometry theory, pore structures of the samples are quantitatively characterized from the aspect of pore distribution, heterogeneity, and anisotropy (represented by three main fractal geometric parameters: fractal dimension, lacunarity, and succolarity, respectively). As a comparison, the binarized CT images of two conventional sandstone cores are simulated with the same parameters. The results show that the correlation between porosity and permeability of the hydrate samples is poor, while there is a strong correlation among the succolarity and the permeability. Fractal dimension (represents complexity) of clayey silt samples is higher compared with conventional sandstone cores. Lacunarity explains the difference in permeability among samples from the perspective of pore throat diameter and connectivity. Succolarity indicates the extent to which the fluid in the pore is permeable, which can be used to characterize the anisotropy of pore structures. Therefore, these three fractal parameters clarify the relationship between the microstructure and macroscopic physical properties of clayey silt porous media.